The NBN from 2009 to 2016 and Beyond - A Commentary on Mike Quigley’s June 2016 Address to the Telecommunications Association - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2016)
On 22 June 2016, Mike Quigley, the founding CEO of NBN Co, gave an address to TelSoc on his insights into, and predictions for, the Australian National Broadband Network (NBN).  This article provides a brief summary of his presentation and a commentary on some of the issues raised.  Mr Quigley contended that, if there had not been a hiatus and change of direction after the election of the Coalition government in 2013, the rollout of the NBN would have been completed by December 2021 within a peak funding of $45 billion, broadly in accord with NBN Co’s plans from September 2013.  A major part of the original plan was for fibre to 93% of existing premises within the fixed-line footprint of the NBN.  He noted that the replacement of the fibre plan in 2013 with a multi-technology mix had slowed deployment.  He showed that the Coalition’s assertions while in opposition about the cost and take-up of the NBN had not proved true up to December 2015.  Mr Quigley’s critique also raised a number of issues about the future direction of the NBN, particularly with regard to a future upgrade of technology and greater capacity needs.